Strategi Guru Mata Pelajaran Fiqih dalam Meningkatkan Kemampuan Beribadah Shalat Siswa di MTs Yaqin 1 Kwang Rundun Kecamatan Jerowaru: Fiqh Subject Teacher's Strategy in Improving Students' Prayer Worship Skills at MTs Yaqin 1 Kwang Rundun, Jerowaru District - Abd Quddus al Badani; Suparlan; Fitria Latifatul Husna; Hardianti; Fatimah (Al-Faiza : Journal of Islamic Education Studies, 2026)
Islamic teachings place a high value on education, even holding an educated and knowledgeable person in higher esteem than an uneducated person. This study aims to uncover the strategies used by Islamic Jurisprudence (Fiqh) teachers to improve students' prayer skills. The research method used was qualitative research with a qualitative percentage approach. Data were obtained through observation, interviews, and documentation. The results indicate that several strategies were implemented by teachers, including the use of prayer theory education strategies, demonstrations of prayer practices, routine training in congregational prayer, integration of contextual learning, individual guidance, encouragement and praise, and integration of Islamic values ​​into other learning activities. These strategies aim to enhance students' understanding of the importance of prayer in their daily lives and to help them practice it effectively. The implications of this study are the importance of teachers' role in guiding students in religious aspects and its relevance in the context of religious education in schools.